PEMIKIRAN POLITIK NICCOLO MACHIAVELLI: STUDI KASUS DINASTI UMAYYAH - fahrezy, Alfin falah; Hamid, Rizal Al (UIN Sunan Kalijaga Yogyakarta, 2021)
The Umayyad dynasty was an Islamic caliphate regime after the khulafa urrasydin which managed to maintain its power for 90 years before being overthrown by the Abbasids. This dynasty is famous for its political stability from the beginning of his reign to a systematized public administration and military. Nevertheless, this dynasty raised pros and cons in terms of morality which were considered to deviate from Islamic teachings at least during the political revolution and post-Caliph Mu'awiyah. The author tries to examine the practice of such government using the political theory of Niccolo Machiavelli in which there are also thoughts about the ethics of power. This study tries to answer several questions, namely what is the ideal government practice in the book